The Abdominal Fascial Closure in a Double-Breasted Jacket Pattern Following a TRAM Free Flap Breast Reconstruction - Kim, Young Seok; Yoo, Han-Su; Hong, Jong Won; Lew, Dae hyun; Roh, Tai Suk (Journal of Reconstructive Microsurgery, 2014)
The primary closure of abdominal fascia after breast reconstruction with transverse rectus abdominis myocutaneous (TRAM) flap has been reported to be the most effective way to reduce these complications. A total of 108 patients who underwent immediate unilateral breast reconstruction with muscle-sparing TRAM flap were included in the study. We compared complications between 56 patients who underwent conventional primary fascial closure (group 1) and 52 who underwent fascial closure in a new double-breasted jacket pattern (group 2), retrospectively. Abdominal bulging occurred in four patients (7.1%) in group 1 and one patient (1.9%) in group 2 (p = 0.01). An abdominal wound dehiscence occurred in three (5.4%) patient in group 1 and two (3.8%) patient in group 2 (p = 0.12). After conventional or muscle-sparing TRAM free flap reconstruction, closing the abdominal fascia in a double-breasted jacket pattern can help reinforce the lower abdominal fascia and prevent abdominal bulging caused by abdominal fascia tensional imbalance.
Keywords: TRAM; abdominal fascial closure; abdominal bulging